Synthesis and antioxidant evaluation of some new sulphadimidine incorporating thiophene moiety - Gouda, Moustafa Ahmed; Eldien, Hadeer Fakhr; Girges, Margret Mansour; Berghot, Moged Ahmed (European Journal of Chemistry, 2014)
A few new sulphadimidine incorporating thiophene moiety are synthesized. These compounds were assessed by analytical and spectral data. Antioxidant evaluation for the investigated compounds was evaluated by ABTS assay and bleomycin-dependent DNA-damage; the compounds exhibited weak activities.